Integrated 3D forward stratigraphic and petroleum system modeling of the Levant Basin, Eastern Mediterranean. (13th December 2018) - Barabasch, Jessica; Ducros, Mathieu; Hawie, Nicolas; Bou Daher, Samer; Nader, Fadi Henri; Littke, Ralf
Abstract: The Eastern Mediterranean Levant Basin is a proven hydrocarbon province with recent major gas discoveries. To date, no exploration wells targeted its northern part, in particular the Lebanese offshore. The present study assesses the tectono‐stratigraphic evolution and related petroleum systems of the northern Levant Basin via an integrated approach that combines stratigraphic forward modeling and petroleum systems/basin modeling based on the previous published work. Stratigraphic modeling results provide a best‐fit realisation of the basin‐scale sedimentary filling, from the post‐rift Upper Jurassic until the Pliocene. Simulation results suggest dominant eastern marginal and Arabian Plate sources for Cenozoic siliciclastic sediments and a significant contribution from the southern Nilotic source mostly from Lower Oligocene to Lower Miocene. Basin modeling results suggest the presence of a working thermogenic petroleum system with mature source rocks localised in the deeper offshore. The generated hydrocarbons migrated through the deep basin within Jurassic and Cretaceous permeable layers towards the Latakia Ridge in the north and the Levant margin and offshore topographic highs. Furthermore, the basin model indicates a possibly significant influence of salt deposition during Messinian salinity crisis on formation fluids. Ultimately, the proposed integrated workflow provides a powerful tool for the assessment of petroleum systems in underexplored areas.